2017
DOI: 10.1111/pbi.12685
|View full text |Cite
|
Sign up to set email alerts
|

Indel‐seq: a fast‐forward genetics approach for identification of trait‐associated putative candidate genomic regions and its application in pigeonpea (Cajanus cajan)

Abstract: Identification of candidate genomic regions associated with target traits using conventional mapping methods is challenging and time‐consuming. In recent years, a number of single nucleotide polymorphism (SNP)‐based mapping approaches have been developed and used for identification of candidate/putative genomic regions. However, in the majority of these studies, insertion–deletion (Indel) were largely ignored. For efficient use of Indels in mapping target traits, we propose Indel‐seq approach, which is a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…(Color figure online) involve re-sequencing genomes of genotypes contrasting in trait phenotype together with detection of nonsynonymous sequence variants have been found to be efficient for rapid identification of potential candidate genes controlling complex traits in pigeonpea and other crops (Silva et al 2012;Xu et al 2014;Singh et al 2016aSingh et al , b, 2017. The results obtained from our previous NGS-based trait mapping studies (Singh et al 2016b(Singh et al , 2017) have encouraged us to use similar approach for identification of candidate genes/markers associated with SPC in pigeonpea.…”
Section: Discussionmentioning
confidence: 99%
“…(Color figure online) involve re-sequencing genomes of genotypes contrasting in trait phenotype together with detection of nonsynonymous sequence variants have been found to be efficient for rapid identification of potential candidate genes controlling complex traits in pigeonpea and other crops (Silva et al 2012;Xu et al 2014;Singh et al 2016aSingh et al , b, 2017. The results obtained from our previous NGS-based trait mapping studies (Singh et al 2016b(Singh et al , 2017) have encouraged us to use similar approach for identification of candidate genes/markers associated with SPC in pigeonpea.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, non-coding RNA, including microRNA and long non-coding RNA (lncRNA), have received attention for their regulatory role in the expression of various genes controlling complex traits at the post-transcriptional level, including for drought stress in chickpea (Khandal et al, 2017;Singh et al, 2017). A microRNA (miRNA) profiling study of root apical meristem identified 284 unique miRNA sequences; of which 259 were differentially expressed under drought and salinity stress (Khandal et al, 2017).…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%
“…Another common trait mapping approach is bulked segregant analysis (BSA) where marker screening on the extreme bulks and parents provides trait-associated markers (see Semagn et al 2010). With the advantage of NGS technologies and draft genome sequence, rapid trait mapping has been performed for sterility mosaic disease (SMD) and fusarium wilt (FW) (Singh et al 2015(Singh et al , 2017. These approaches depend on extreme bulks and NGS to even provide markers for qualitative and quantitative traits.…”
Section: Rapid Detection Of Markers Associated With Traitsmentioning
confidence: 99%